Treatment of symptomatic endobronchial hamartoma by bronchoscopy - María Emilia Cano; Felipe Pagnoncelli Fachin; José Carlos Felicetti (Revista de la Facultad de Ciencias Médicas de Córdoba)
Hamartomas are benign tumors characterized by disorganized tissue native to a specific anatomical location. We present the case of a 61-year-old male with a history of COVID-19 infection who presented with a persistent cough. Chest tomography revealed an endobronchial lesion, which led to further investigation with a bronchoscopy. Using a cold loop, the lesion was successfully resected and pathology confirmed the diagnosis of a hamartoma.  Endobronchial resection is the preferred strategy for diagnosing and treating these tumors. This case highlights the successful management of an endobronchial hamartoma in a patient with a history of COVID-19 infection, emphasizing the importance of thorough investigation and appropriate intervention in similar cases.